Implicit development of gaze strategies support motor improvements during action encoding training of prosthesis use. (April 2019) - Bayani, Kristel Y.; Lawson, Regan R.; Levinson, Lauren; Mitchell, Sarah; Atawala, Neel; Otwell, Malone; Rickerson, Beth; Wheaton, Lewis A.
Abstract: Background: Action observation training has been suggested to facilitate motor improvements in the lives of persons with neural injury. Previous studies have shown that for persons with upper limb amputation, matched limb training, where prosthesis users emulate each other, has shown promise above mismatched training where a prosthesis user emulates actions of a person with sound limbs (most commonly that of a therapist). Objective: The mechanism underlying the matched limb training benefit is unclear. Gaze strategies may reveal unique patterns between matched and mismatched training which could explain improvements in motor function in matched limb training. Methods: Twenty persons with sound limbs were trained on how to use a prosthesis simulator using matched or mismatched limb training in a single session. Eye movements were recorded during the training phase. Kinematics were recorded as persons performed the task. Results: Gaze patterns showed differences between the training groups. The mismatched group demonstrated a higher probability of gaze on the path between the start and end of the action, while the matched group demonstrated a significantly higher probability of focusing on the elements of the path of the action and a trend of focusing on the shoulders. Kinematics also revealed overall improvements in motor control for the matched group. Conclusions: This study proposes a putative mechanism that may explain improvements in matched limb training through shifting gaze strategies. Further work is needed to understand whether implicit visual strategies seen during matched limb training might encourage motor learning during functional training with prostheses. Highlights: We sought to understand the role that gaze behavior plays on action observation. Persons trained by observing a prosthesis user (matched) or sound limb (mismatched). Matched training shows gaze focused on task-specific control of user and prosthesis. Gaze in matched observation may facilitate kinematic performance with prostheses.